2011
DOI: 10.1002/eji.201141561
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐differentiated human committed T‐lymphoid progenitors promote peripheral T‐cell re‐constitution after stem cell transplantation in immunodeficient mice

Abstract: T‐cell re‐constitution after allogeneic stem cell transplantation (alloSCT) is often dampened by the slow differentiation of human peripheral blood CD34+ (huCD34+) hematopoietic stem cells (HSCs) into mature T cells. This process may be accelerated by the co‐transfer of in vitro‐pre‐differentiated committed T/NK‐lymphoid progenitors (CTLPs). Here, we analysed the developmental potential of huCD34+ HSCs compared with CTLPs from a third‐party donor in a murine NOD‐scid IL2Rγnull model of humanised chimeric haema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Nevertheless, it appears that this population of CLPs is skewed toward a B lymphocyte fate, whereas cord blood progenitors with a CD34þCD7þCD45RAþ phenotype express T/NK cell lineage-affiliated genes and show enhanced T lineage differentiation potential [44]. Furthermore, recent studies have demonstrated that following ex vivo Notch ligand stimulation of CD34þ progenitors, it is the differentiated CD34þCD7þ CD45RAþ CLP subset that displays augmented in vivo thymus colonization and a more rapid T-cell differentiation than conventional CD34þ progenitors [45][46][47]. Thus, the precursors that settle the human thymus under physiological conditions are likely to share this CD34þCD7þCD45RAþ phenotype.…”
Section: Hematopoietic Precursor Differentiation Within the Thymusmentioning
confidence: 99%
“…Nevertheless, it appears that this population of CLPs is skewed toward a B lymphocyte fate, whereas cord blood progenitors with a CD34þCD7þCD45RAþ phenotype express T/NK cell lineage-affiliated genes and show enhanced T lineage differentiation potential [44]. Furthermore, recent studies have demonstrated that following ex vivo Notch ligand stimulation of CD34þ progenitors, it is the differentiated CD34þCD7þ CD45RAþ CLP subset that displays augmented in vivo thymus colonization and a more rapid T-cell differentiation than conventional CD34þ progenitors [45][46][47]. Thus, the precursors that settle the human thymus under physiological conditions are likely to share this CD34þCD7þCD45RAþ phenotype.…”
Section: Hematopoietic Precursor Differentiation Within the Thymusmentioning
confidence: 99%
“…Nevertheless, it appears that this population of CLPs is skewed toward a B lymphocyte fate, whereas cord blood progenitors with a CD34+CD7+CD45RA+ phenotype express T/NK cell lineage‐affiliated genes and show enhanced T lineage differentiation potential [44]. Furthermore, recent studies have demonstrated that following ex vivo Notch ligand stimulation of CD34+ progenitors, it is the differentiated CD34+CD7+ CD45RA+ CLP subset that displays augmented in vivo thymus colonization and a more rapid T‐cell differentiation than conventional CD34+ progenitors [45–47]. Thus, the precursors that settle the human thymus under physiological conditions are likely to share this CD34+CD7+CD45RA+ phenotype.…”
Section: Hematopoietic Precursor Differentiation Within the Thymusmentioning
confidence: 99%
“…Notch‐1 signaling plays a major role for priming human stem cells (HSCs) toward the T‐cell lineage and thus for early thymopoiesis [9–11]. Notch‐based culture systems, such as delta‐like‐1 (DL‐1)‐expressing BM stromal cells (OP9/DL‐1 cells), allow in vitro generation of large numbers of human T‐cell progenitors that have been demonstrated to promote de novo thymopoiesis in humanized mice [12–14]. This working hypothesis was further supported by observations in conventional mouse models: when transferred into allogeneic recipients, murine T‐cell progenitors generated in OP9/DL‐1 coculture accelerated de novo thymopoiesis and emergence of host‐tolerant, functional T cells that afforded protection against infectious agents and residual tumor cells when transferred into an allogeneic HSCT model [15, 16].…”
Section: Introductionmentioning
confidence: 99%